2011
DOI: 10.1530/eje-10-0996
|View full text |Cite
|
Sign up to set email alerts
|

Assessing adrenal status in patients before and immediately after coronary artery bypass graft surgery

Abstract: Objective: Patients with cortisol deficiency poorly tolerate any systemic inflammatory response syndrome (SIRS), and may die if not treated with sufficient exogenous glucocorticoids. Controversy surrounds what constitutes a 'normal' adrenal response in critical illness. This study uses conventional tests for adrenal insufficiency to investigate cortisol status in patients undergoing elective coronary artery bypass surgery, a condition frequently associated with SIRS. Design: A prospective, observational study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…Our results are consistent with those of previous reports assessing postoperative adrenal function in cardiac surgery patients. Two previously published studies have reported a 25% and 27% rate of postoperative RAI in, respectively, 30 patients and 45 patients undergoing coronary artery bypass graft surgery [12,13]. In comparison, the prevalence of RAI in our study was 56% in a cohort of 135 patients.…”
Section: Commentcontrasting
confidence: 50%
See 1 more Smart Citation
“…Our results are consistent with those of previous reports assessing postoperative adrenal function in cardiac surgery patients. Two previously published studies have reported a 25% and 27% rate of postoperative RAI in, respectively, 30 patients and 45 patients undergoing coronary artery bypass graft surgery [12,13]. In comparison, the prevalence of RAI in our study was 56% in a cohort of 135 patients.…”
Section: Commentcontrasting
confidence: 50%
“…Neither of those studies [12,13] assessed the impact of RAI on postoperative hemodynamic status. In contrast, a recently published study by Irribaren and colleagues [15] examined the impact of RAI on postoperative vasopressor requirements in 120 cardiopulmonary bypass surgery patients.…”
Section: Commentmentioning
confidence: 99%
“…Right after, ACTH declines rapidly to normal levels, while cortisol levels decrease slowly, reaching high normal values 48 to 72 hours after the procedure. 125,127,129 This has been confirmed in coronary artery bypass graft operations, although not by all studies, 130 where basal and stimulated cortisol levels have been correlated with severity of stress, peaking shortly after extubation and being similar to levels during other major surgical procedures and critical illness. 131,132 Studies demonstrate that this principally occurs through cytokine regulation of the HPA axis primarily by direct or indirect stimulation of hypothalamic CRH, especially by IL-1, IL-6, and TNF-α, and also by directly affecting the pituitary and adrenal glands.…”
Section: 128mentioning
confidence: 89%
“…Cortisol concentrations do not reflect adrenal function and are affected by hypoproteinemia [13]. The synthetic ACTH test is less reliable and at risk of showing a false positive in the postoperative phase, as exemplified by Debono et al [14,15]. Therefore, it is recommended to treat the patient with glucocorticoids when adrenal insufficiency is clinically suspected [15].…”
Section: Discussionmentioning
confidence: 99%